2007
DOI: 10.1182/blood-2006-10-053181
|View full text |Cite
|
Sign up to set email alerts
|

Arginine 595 is duplicated in patients with acute leukemias carrying internal tandem duplications of FLT3 and modulates its transforming potential

Abstract: FLT3-internal tandem duplications (FLT3-ITDs IntroductionMutations in the FMS-like tyrosine-kinase 3 (FLT3) are one of the most frequently found genetic alterations in patients with acute myeloid leukemia (AML), 1-13 myelodysplastic syndromes (MDSs; 10%-15%), 2,14 and acute lymphoblastic leukemia (ALL; 1%-3%). 9,16,17 FLT3 belongs to the class III of receptor tyrosine kinases, which are characterized by the presence of an extracellular immunoglobulin-like domain, a transmembrane and the cytoplasmic juxtamembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Kiyoi et al hypothesized that the DNA sequence between amino acids 593 and 602 forms a palindromic intermediate that leads to a DNA replication error, thus inducing the tandem duplication. 37 Other investigators showed that 95% of the patients with FLT3-ITD mutations contained at least one amino acid of the tyrosine-rich stretch Y591 to Y599 30 and that the amino acid residue R595 may play an essential role in activation of STAT5. 30 In addition, tyrosine to phenylalanine substitution of residues 589 and 591 abrogates STAT5 activation of FLT3-ITD, and FLT3-ITD-Y589/591F is incapable of inducing a myeloproliferative phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kiyoi et al hypothesized that the DNA sequence between amino acids 593 and 602 forms a palindromic intermediate that leads to a DNA replication error, thus inducing the tandem duplication. 37 Other investigators showed that 95% of the patients with FLT3-ITD mutations contained at least one amino acid of the tyrosine-rich stretch Y591 to Y599 30 and that the amino acid residue R595 may play an essential role in activation of STAT5. 30 In addition, tyrosine to phenylalanine substitution of residues 589 and 591 abrogates STAT5 activation of FLT3-ITD, and FLT3-ITD-Y589/591F is incapable of inducing a myeloproliferative phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…37 Other investigators showed that 95% of the patients with FLT3-ITD mutations contained at least one amino acid of the tyrosine-rich stretch Y591 to Y599 30 and that the amino acid residue R595 may play an essential role in activation of STAT5. 30 In addition, tyrosine to phenylalanine substitution of residues 589 and 591 abrogates STAT5 activation of FLT3-ITD, and FLT3-ITD-Y589/591F is incapable of inducing a myeloproliferative phenotype. 31 Interestingly, we showed that in 96.1% of all analyzed FLT3-ITDs at least one amino acid of this motif (Y591-Y599) was affected, and this was independent of ITD length and insertion site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter may involve a frameshift and affect transcriptional activity, especially for some critical codons. 23 In summary, our study indicates that FLT3-ITD is a common genetic alteration in Chinese adult patients with AML. Multivariate analysis shows that the ITD to wildtype ratio, the gene patterns, and CD7 expression status appear to be independent prognostic indices for patients with AML.…”
Section: Multivariate Analysis Of Prognostic Factorsmentioning
confidence: 99%
“…The most common abnormalities, occurring in approximately 23 % of newly diagnosed de novo AML, are the FLT3/ITD mutations [6]. These mutations consist of in-frame tandem duplications of coding sequence, almost always encompassing arginine residue 595 within the juxtamembrane domain [16]. The juxtamembrane domain of RTKs often has an autoinhibitory function [17].…”
Section: Flt3 Receptor In Amlmentioning
confidence: 99%